The Role of Registered Certificate (SKT) as an Instrument of Legal Protection in Indonesian Tax Administration - Muchamad Catur Rizky; Sudjai; Didit Darmawan (Universitas Muhammadiyah Palu, 2025)
This study provides a normative legal analysis of the role and challenges of the Certificate of Registration (Surat Keterangan Terdaftar or SKT) as a fundamental legal instrument in Indonesia’s tax administration system. The SKT serves not only as proof of legal authority but also marks the commencement of a taxpayer’s formal tax obligations, whether for individuals or legal entities. Employing a regulatory review approach combined with scholarly literature and relevant legal doctrines, the study reveals that although the SKT is designed to uphold the principle of legality and strengthen the administrative validity of taxation, several practical issues persist. These include inconsistent interpretations, inefficient bureaucratic procedures, and the need for adaptation to digital systems and inter-agency data integration. Such challenges can lead to miscommunication, administrative oversight, and legal vulnerabilities for both taxpayers and tax authorities. To address these concerns, the study recommends regulatory harmonization, enhanced taxpayer education, stronger oversight mechanisms, and improved data verification and security systems. Streamlining administrative procedures and conducting periodic evaluations are essential to reinforce the SKT as a tool for legal protection and certainty within the national tax framework. These findings aim to offer both theoretical insight and practical recommendations for advancing tax law and improving fiscal administrative governance in Indonesia towards a more accountable and equitable system.